Intervensi Pekerjaan Sosial Terhadap Perempuan Rawan Sosial Ekonomi dalam Keluarga Pra-Sejahtera Melalui Edukasi Keluarga Berencana di BKKBN Provinsi Sumatera Utara - Fadel Muhammad Revaldo; Agus Suriadi (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Women with socio-economic vulnerabilities in pre-prosperous families are a group that is highly susceptible to various social problems due to limited economic resources, low access to information, and heavy family responsibilities. These conditions can affect a family's ability to plan family life effectively, including making informed decisions regarding family planning. This study aims to describe the social work intervention process for socio-economically vulnerable women in pre-prosperous families through family planning services at the National Population and Family Planning Agency (BKKBN) of North Sumatra Province. The study employed a qualitative method with a case study approach. Data were collected through observation, interviews, and documentation during the field practicum. Case analysis was conducted using the Person-in-Environment (PIE) approach to understand the relationship between individual conditions and their social environment, as well as the Strengths Perspective to identify the client’s potential and strengths in addressing her problems. The findings indicate that the client’s primary issues were related to limited family economic conditions, insufficient understanding of family planning, and concerns about the use of contraceptive methods. Social work interventions were implemented through the stages of engagement, assessment, planning, intervention, evaluation, and termination. The interventions included education, counseling, information dissemination, and motivational support. The results showed an improvement in the client’s understanding of the importance of family planning, the benefits of contraceptive use, and the relationship between family planning and family welfare.